BOOK OF FLASHBACKS OF ROMAN YAREMIYCHUK - Вольвач, Павло (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Review of Roman Yaremiychuk’s book "Past – is not our own already ". – Simferopil’: "Tavriya", 2010. - 516 p.